Causes and trends of water scarcity in food production. (8th January 2016) - Porkka, Miina; Gerten, Dieter; Schaphoff, Sibyll; Siebert, Stefan; Kummu, Matti
Abstract: The insufficiency of water resources to meet the needs of food production is a pressing issue that is likely to increase in importance in the future. Improved understanding of historical developments can provide a basis for addressing future challenges. In this study we analyse how hydroclimatic variation, cropland expansion and evolving agricultural practices have influenced the potential for food self-sufficiency within the last century. We consider a food production unit (FPU) to have experienced green–blue water (GBW) scarcity if local renewable green (in soils) and blue water resources (in rivers, lakes, reservoirs, aquifers) were not sufficient for producing a reference food supply of 3000 kcal with 20% animal products for all inhabitants. The number of people living in FPUs affected by GBW scarcity has gone up from 360 million in 1905 (21% of world population at the time) to 2.2 billion (34%) in 2005. During this time, GBW scarcity has spread to large areas and become more frequent in regions where it occurs. Meanwhile, cropland expansion has increased green water availability for agriculture around the world, and advancements in agronomic practices have decreased water requirements of producing food. These efforts have improved food production potential and thus eased GBW scarcity considerably but also made possible the rapid population growth of the last century. The influence of modern agronomic practices is particularly striking: if agronomic practices of the early 1900s were applied today, it would roughly double the population under GBW scarcity worldwide.